THE UNITY OF INDONESIA - Narny, Yenny (Prodi. Pendidikan Sejarah FPIPS UPI dan APPS (Asosiasi peneliti dan Pendidik Sejarah), 2011)
Since independence Indonesia’s military has played an active role in defending the territorial integrity of Indonesia. For example, the military has been used to put down rebellions in various regions, such as Darul Islam in West Java in 1948, the Acehnese rebellion that was led by Daud Beurueh in 1950, Pemerintah Revolusioner Republik Indonesia (PRRI), the Revolutionary Government of the Indonesian Republic) in West Sumatra in 1958, and Piagam Perjuangan Semesta Alam (Permesta) Charter of Universal Struggle in North Sulawesi in 1958. Disagreements with central government policies were the cause of these rebellions since they were intended to change the central government, not to achieve separatism. In addition, in 1961 a military operation was used to support the claim of Indonesia to West Irian (now Papua). By carrying out a military operation and negotiating with those giving support from the United States, in 1969 Indonesia succeeded in its goal of claiming Papua as a part of Indonesia. The success in pulling Papua into Indonesia’s territory did not directly stop the military operation there because the military had to maintain order in the region to frustrate the Organisasi Papua Merdeka (OPM), Free Papuan Organisation, separatist movement that began in 1964 and continues to the present day